2014
DOI: 10.1016/j.cell.2014.05.039
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Chaperone Interaction Network Reveals the Architecture of Cellular Protein Homeostasis Pathways

Abstract: Chaperones are abundant cellular proteins that promote the folding and function of their substrate proteins (clients). In vivo, chaperones also associate with a large and diverse set of co-factors (co-chaperones) that regulate their specificity and function. However, how these co-chaperones regulate protein folding and whether they have chaperone-independent biological functions is largely unknown. We have combined mass spectrometry and quantitative high-throughput LUMIER assays to systematically characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
407
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(424 citation statements)
references
References 64 publications
12
407
2
3
Order By: Relevance
“…A growing body of evidence implies that NudC functions as a co-chaperone of Hsp90 to stabilize client proteins [16][17][18]. Proteomics data from our laboratory and others indicate that NudC may interact with cofilin 1 [17,18], a key regulator of actin dynamics, yet little is known about the role of NudC in actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…A growing body of evidence implies that NudC functions as a co-chaperone of Hsp90 to stabilize client proteins [16][17][18]. Proteomics data from our laboratory and others indicate that NudC may interact with cofilin 1 [17,18], a key regulator of actin dynamics, yet little is known about the role of NudC in actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 96%
“…Mass spectrometry data of proteins co-immunoprecipitated with NudC reported by our group and others have indicated that cofilin 1 may interact with NudC [17,18]. The similar roles of NudC and cofilin 1 in actin dynamics prompted us to investigate the biochemical interaction between these two proteins [28][29][30].…”
Section: Nudc Binds To and Stabilizes Cofilinmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 Several proteins involved in DNA repair and replication are well-characterized clients of molecular chaperones. 38 Specifically Hsp90 contributes to genomic integrity, as it is an essential factor for telomerase activity. 39 Hsp90 inhibition also sensitizes human cells to UV-induced cytotoxicity due to impaired function of Pol h 40 and leads to accumulation of chromosomal aberrations due to FancA degradation.…”
Section: Causes Of the Downregulation Of Dna Replication Factors In Amentioning
confidence: 99%
“…They prevent protein aggregation and/or stimulate folding towards the native state. Chaperones often interact with co-chaperones (186). After release of a protein from the ribosome, its folding may also be affected by chaperones.…”
Section: Protein Folding In Vivomentioning
confidence: 99%